The Relationship between Cyber Violence and Cyber Sex Crimes: Understanding the Perception of Cyber Sex Crimes as Systemic Issues - Eugene Lee; Hye Eun Lee (MDPI AG, 2024)
This study examines the relationship between cyber violence and cyber sex crimes, specifically focusing on these crimes as systemic issues among adolescents. The research highlights the severe impact of cyber sex crimes, characterized by the non-consensual sharing of sexually explicit content. It examines various factors that may contribute to witnessing cyber sex crimes, including exposure to violent online content, personal experiences of cyber violence (either as a victim or perpetrator), and the role of parental and teacher interventions. Utilizing data from a nationwide survey conducted by the Korea Communications Commission, the study analyzes responses from 9016 adolescents in 2021 and 9693 in 2022. This analysis reveals significant predictors of witnessing cyber sex crimes and examines how perceptions of cyber violence and interventions of authoritative figures may influence adolescents' perception of cyber sex crimes as either systemic or individual issues. With females disproportionately affected, the findings underscore a gendered aspect of cyber violence. Furthermore, these insights suggest that perceiving cyber violence as a serious issue leads to viewing cyber sex crimes as systemic problems necessitating societal intervention. The study advocates for enhanced digital literacy education and systemic changes to protect adolescents from the widespread threats of cyber violence and sex crimes.